Comparison of hysterectomy cases performed via conventional laparoscopy or vaginally assisted natural orifice transluminal endoscopic surgery: a paired sample cross-sectional study. (3rd April 2021) - Kaya, Cihan; Alay, Ismail; Cengiz, Huseyin; Yıldız, Gunes Ozlem; Baghaki, Hayriye Sema; Yasar, Levent
Abstract: Hysterectomy is one of the most frequent gynaecological procedures performed for various uterine pathologies. There are several approaches for conducting hysterectomies, including abdominal, vaginal, laparoscopic and robotic. Recently, natural orifices transluminal endoscopic surgery (NOTES) has emerged as an alternative approach for conducting hysterectomies. In this study, we aimed to compare the results of total laparoscopic hysterectomy (TLH) and vaginally assisted-NOTES (vNOTES) hysterectomy procedures for the treatment of benign gynaecological diseases. Ninety-nine patients, who underwent conventional TLH or vNOTES hysterectomies, were included in this study. The operation time, presence of per/postoperative complications, visual analogue scale (VAS) scores at postoperative sixth and 24th hours, and the duration of hospital stays were all analysed. The duration of surgery was significantly shorter in the vNOTES hysterectomy group (79.56 ± 32.54 min) compared to the TLH group (120.67 ± 38.35 min) ( p : < .001). Also, postoperative hospital stays were significantly shorter in favour of the vNOTES hysterectomy group (44 ± 16.47 h) compared to the TLH group (57.86 ± 21.31 h) ( p : .002). These results indicate that vNOTES hysterectomy can be a promising approach for treating a variety of different uterine pathologies and, furthermore, that it can be an alternative to TLH. Impact statement: What is already known on this subject? A hysterectomy can be done in a variety of different ways, such as abdominal, laparoscopic, vaginal, and robotic. Even though the standard practice guidelines recommend that a vaginal hysterectomy (VH) should be the first choice of treatment, it can be challenging in cases of non-descendent and large uteruses. In such cases, NOTES hysterectomy can be an alternative option. What do the results of this study add? The study has shown that vNOTES is associated with a shorter operation and briefer postoperative hospitalisation time, in comparison to TLH. What are the implications of these findings for clinical practice and/or further research? This study speculates that vNOTES is an approach which may offer better outcomes than a conventional laparoscopy. Further randomised controlled trials with larger sample sizes, however, should be conducted in order to establish the place of vNOTES in hysterectomy surgeries.